Assessing the Implementation of the Pancasila Student Profile (P5) Project on Local Wisdom in Vocational High Schools: A CIPP Model Evaluation - Ariska Dwi Putri; Muhammad Adri; Arwizet Arwizet; Muhammad Giatman (AL-ISHLAH: Jurnal Pendidikan, 2026)
The Pancasila Student Profile Strengthening Project (P5), a core component of Indonesia’s Merdeka Curriculum, aims to integrate character education with contextual learning. This study evaluates the implementation of a local wisdom–themed P5 project in a Vocational High School (SMK) in West Sumatra, focusing on its effectiveness in aligning cultural values with vocational competencies.A sequential explanatory mixed-methods design was employed using the CIPP (Context, Input, Process, Product) evaluation model. Data were collected from 155 participants (principals, teachers, and students) through questionnaires, interviews, observations, and document analysis. Quantitative data were analyzed descriptively, followed by qualitative interpretation to explain key findings.The context evaluation demonstrated strong alignment with national education policies. Input analysis revealed a disparity between adequate facilities (82%) and limited teacher understanding of program management (63%). During implementation, student participation was moderate (73%), but inconsistent pedagogical facilitation hindered effectiveness. Product evaluation indicated a positive yet suboptimal impact on student character development (74%).The findings highlight a critical gap between structural readiness and human resource capacity. Although institutional support and infrastructure are sufficient, limitations in teachers’ pedagogical and managerial competencies constrain program outcomes.The effectiveness of P5 implementation depends less on infrastructure and more on strengthening teacher capacity. Policy efforts should prioritize professional development, practical mentorship, and clear technical guidelines to bridge the gap between curriculum design and classroom practice, thereby optimizing the integration of local wisdom in vocational education.